Apathy in Parkinson`s disease is related to executive function, gender and age but not to depression - Meyer, Antonia; Zimmermann, Ronan; Gschwandtner, Ute; Hatz, Florian; Bousleiman, Habib; Schwarz, Nadine; Fuhr, Peter (Frontiers in Aging Neuroscience, 2015)
Deficits in executive functions occur in up to 93% of patients with Parkinson`s disease (PD). Apathy, a reduction of motivation and goal-directed behavior is an important part of the syndrome; affecting both the patients as well as their social environment. Executive functions can be subdivided into three different processes: initiation, shifting and inhibition. We examined the hypotheses, (1) that apathy in patients with Parkinson`s disease is only related to initiation and not to shifting and inhibition, and (2) that depression and severity of motor signs correlate with apathy. Fifty-one non-demented patients (19 = female) with PD were evaluated for apathy, depression and executive functions. Executive function variables were summarized with an index variable according to the defined executive processes. Linear regression with stepwise elimination procedure was used to select significant predictors. The significant model (R2 = .41; p < .01) revealed influences of initiation (b = - .79; p < .01), gender (b = - 7.75; p < .01), age (b = -.07; p < .05) and an age by gender interaction (b = .12; p < .01) on apathy in Parkinson`s disease. Motor signs, depression and level of education did not influence the relation. These results support an association of apathy and deficits of executive function in PD. Initiation strongly correlates with apathy, whereas depression does not. We conclude, that initiation dysfunction in a patient with Parkinson`s disease heralds apathy. Apathy and depression can be dissociated. Additionally, apathy is influenced by age and gender: older age correlates with apathy in men, whereas in women it seems to protect against it.